2017
DOI: 10.1016/j.biortech.2016.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient bead milling of microalgae: Effect of bead size on disintegration and release of proteins and carbohydrates

Abstract: The disintegration of three industry relevant algae (Chlorella vulgaris, Neochloris oleoabundans and Tetraselmis suecica) was studied in a lab scale bead mill at different bead sizes (0.3-1mm). Cell disintegration, proteins and carbohydrates released into the water phase followed a first order kinetics. The process is selective towards proteins over carbohydrates during early stages of milling. In general, smaller beads led to higher kinetic rates, with a minimum specific energy consumption of ⩽0.47kWhkg for 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 28 publications
9
110
2
Order By: Relevance
“…; Postma et al . ). Bead mills have been successfully applied for the disintegration of microalgae for the release of intracellular products (Doucha & Livansky ; Schwenzfeier et al .…”
Section: Downstream Processing and Recovery Of Astaxanthinmentioning
confidence: 97%
See 1 more Smart Citation
“…; Postma et al . ). Bead mills have been successfully applied for the disintegration of microalgae for the release of intracellular products (Doucha & Livansky ; Schwenzfeier et al .…”
Section: Downstream Processing and Recovery Of Astaxanthinmentioning
confidence: 97%
“…ceramic, glass and steel) that are agitated at high speeds resulting in multiple collisions. The dried biomass is fed in these chambers, and cells are disrupted in the bead collision zones by (2010) compaction and shear forces (Jahanshahi et al 2002;Shah et al 2016;Postma et al 2017). Bead mills have been successfully applied for the disintegration of microalgae for the release of intracellular products (Doucha & Livansky 2008;Schwenzfeier et al 2011;Postma et al 2015;Gunerken et al 2016).…”
Section: Downstream Processing and Recovery Of Astaxanthinmentioning
confidence: 99%
“…A straight comparison of the energy requested by different disruption technique is a difficult task since each individual study relies on a specific and individual diagnostic. As a guide, one can still note that in the current state of the art, the lowest reported values for BM are in the range of 1.6 to 3.6 MJ/kgDW (Postma et al, 2017(Postma et al, , 2015. In the case of HPH, values as low as 0.16 MJ/kgDW have been reported for weak species, while resistant species, such as Nannochloropsis, still require at least around 3.4 MJ/kgDW when treated directly after harvesting.…”
Section: Introductionmentioning
confidence: 98%
“…Other factors include bead size, cell size, and its strength [22]. Study on disruption of Chlorella vulgaris, Neochloris oleoabundans, and Tetraselmis suecica revealed that rate of release of intracellular carbohydrates and protein was higher with minimum energy consumption for smaller sized beads [23]. The rate of cell disruption is also directly proportional to volume ratio of the beads to that of cell suspension [24].…”
Section: Bead Millingmentioning
confidence: 99%